Geografia e filosofia. Riflessioni su Pensiero vivente di Roberto Esposito a partire da Spinoza, Cavell e Foucault - Raffaele Ariano (Rosenberg & Sellier, 2019)
The article focuses on the so-called ‘Italian theory’, with special reference to its assessment in Roberto Esposito’s 2010 book Living Thought. The article puts forth three main arguments. First, there is an analogy between the ‘geo-philosophical’ strategy chosen by Esposito to address Italian thought and the strategy pursued by Stanley Cavell when he reflects on Emerson and the specificity of American philosophy. Second, the main traits attributed by Esposito to Italian thought show significant parallels with key concepts in Michel Foucault’s philosophy. Third, interpretations of Spinoza by authors such as Gilles Deleuze and Toni Negri have been instrumental for the flourishing of the philosophical debate that prepared Esposito’s elaboration of a canon of Italian thinkers. The article thus hints that Italian theory could be an interesting case study for the reflection on the relations between geography and philosophy.